Legal Status and Functions of the Prosecutor’s Office: European Experience - NALUTSYSHYN, Viktor (University Scientific Notes, 2021)
Comprehensive scientific analysis of the legal status and powers of prosecutors in European countries has been conducted. The position of the prosecutor’s office in the system of the state mechanism of the European countries has been investigated. The main criteria for determining the place of the prosecutor’s office in the system of state bodies have been given. Depending on the position occupied by the prosecutor’s office in the system of state bodies, four groups of states have been distinguished: 1) states where the prosecutor’s office is part of the Ministry of Justice (Austria, Belgium, Denmark, France, Germany, the Netherlands, Poland); 2) states where the prosecutor’s office is included in the judiciary (magistracy) and is in the courts (Bulgaria, Spain, Italy); 3) states where the prosecutor’s office is allocated to a separate system and is accountable to parliament (Slovakia, Hungary); 4) states where the prosecutor’s office as an independent body of the state is absent (England). It is stated that the issues of organization and activity of prosecutor’s offices in European countries are solved at the national level, but taking into account the common standards of functioning of prosecutor’s offices, which are developed at the international, supranational and regional levels. It is determined that the basic norms concerning the functioning of the prosecutor’s office in European countries are provided mainly in the acts of procedural legislation. It has been found that the prosecutor’s office in European countries has a fairly wide range of powers. They prosecute, monitor the activities of investigating judges and the judicial police, support prosecutions in court, participate in civil cases when the public interest so requires, and exercise many other powers provided by law to regulate the activities of the prosecutor’s office. It is concluded that the principles of objectivity, impartiality and independence of the prosecutor’s office are enshrined and implemented in practice in the legislation of almost all European countries. It is concluded that the general trend of development of the Prosecutor’s Office of Ukraine should be the expansion of its functions, non-interference of the legislative and executive authorities in the substantive activities of the Prosecutor’s Office.
Keywords: prosecutor’s office; international experience; legal status; functions of the prosecutor’s office; model of the prosecutor’s office; place of the prosecutor’s office